Investigation on the light and elevated temperature induced degradation of gallium-doped Cz-Si. (1st September 2021) - Lin, Dehang; Hu, Zechen; Song, Lihui; Yang, Deren; Yu, Xuegong
Highlights: Gallium-doped Cz-Si wafers suffer from severe LeTID after firing. The degradation consists of a fast and a slow process. The activation energies of LeTID processes are determined according to Arrhenius plots. A possible defect model to explain our experimental findings is proposed. Abstract: In this study, we performed light and elevated temperature induced degradation (LeTID) experiments in gallium-doped Czochralski silicon (Cz-Si) wafers and investigated the impact of temperature on reaction kinetics. The degradation was found to have a fast and a slow process, and their reaction rates were extracted by using an exponential function. We further determined the activation energies of each degradation as well as the regeneration according to Arrhenius plots. Moreover, we found that the capture cross-section ratio of the generated defect remained in the range of 27 <  k  < 35 throughout the degradation. Based on these findings, we suggested that both fast and slow degradation might be attributed to the generation of a same recombination-active defect from different precursors, and consequently have different reaction rates.